2018
DOI: 10.1007/s12975-018-0619-x
|View full text |Cite
|
Sign up to set email alerts
|

HDAC9 Polymorphism Alters Blood Gene Expression in Patients with Large Vessel Atherosclerotic Stroke

Abstract: The histone deacetylase 9 (HDAC9) polymorphism rs2107595 is associated with an increased risk for large vessel atherosclerotic stroke (LVAS). In humans, there remains a need to better understand this HDAC9 polymorphism's contribution to large vessel stroke. In this pilot study, we evaluated whether the HDAC9 polymorphism rs2107595 is associated with differences in leukocyte gene expression in patients with LVAS. HDAC9 SNP rs2107595 was genotyped in 155 patients (43 LVAS and 112 vascular risk factor controls). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Recent genome-wide association studies have identified several genetic variants of HDAC9 associated with carotid intima-media thickness, peripheral arterial disease, CAD, and ischemic stroke of large vessel (Hacke & Grond-Ginsbach, 2012;Malik, et al, 2017;H. S. Markus, et al, 2013;Matsukura, et al, 2015;Shroff, et al, 2018;. By immunohistochemical staining, HDAC9 was mainly expressed in VSMCs and endothelial cells of cerebral and systemic arteries.…”
Section: B Hdac5mentioning
confidence: 99%
“…Recent genome-wide association studies have identified several genetic variants of HDAC9 associated with carotid intima-media thickness, peripheral arterial disease, CAD, and ischemic stroke of large vessel (Hacke & Grond-Ginsbach, 2012;Malik, et al, 2017;H. S. Markus, et al, 2013;Matsukura, et al, 2015;Shroff, et al, 2018;. By immunohistochemical staining, HDAC9 was mainly expressed in VSMCs and endothelial cells of cerebral and systemic arteries.…”
Section: B Hdac5mentioning
confidence: 99%
“…A recent study found that there were significantly gene expression differences between HDAC9 risk allele-positive and negative large vessel atherosclerotic stroke patients, which illustrated that HDAC9 variants may be associated with peripheral immune, lipid, and clotting systems. 35 Whether HDAC9 variants affect IA in a similar manner with that in large vessel atherosclerotic stroke is still unknown. Exact mechanisms should be studied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for determining significantly differentially expressed genes were P < 0.01 and |fold change| ≥ 1.2. A fold change of 1.2 was used as in our previous studies to help ensure biologically significant changes and to provide enough genes for functional pathway analysis …”
Section: Methodsmentioning
confidence: 99%